(untitled) (JOURNAL OF THE FACULTY OF MEDICAL SCIENCES, 2023)
In the span of seven years, in the Hospital "Abel Gilbert Ponton" was operated an average of 6825 patients, of these 2.6% were complicated patients (184 patients) and the main complication was the entero-cutaneous fistula 164 patients is say 2.4%, which would be within the margin percentage international fistula production. (thesis Dr. Fernando Moncayo A.) The co-morbidity factors (62% of the patients in this study had more than 3 factors) influenced the evolution of the patient who underwent surgery, but also the appearance of fistula was observed in patients without them. The patient’s age, nutritional status, comorbid states (cancers, diabetes, inmundeprimido), septic or inflammatory processes that currently owns the patient are gravitating factors (risks) in the occurrence of fistulas. In our study 62% had more than 3 factors. Besides the human factor as the ability to solve problems encountered in surgery, physical and mental fatigue (Burnaut syndrome) are also factors influencing post-surgical complications. Overall mortality was 13.3%, were re-operated for 8.7% of patients and were not re-operated 4.3%.